Kedudukan Naskah Akademis Dalam Perumusan Peraturan Daerah Menurut Undang-Undang Pembentukan Peraturan Perundang-Undangan - Firdaus Arifin (CV Rewang Rencang, 2024)
The process of forming regulations is often not in line with existing theories. Based on Article 56 paragraph (2) of Law Number 12 of 2011, it basically states that Regional Regulations need to be accompanied by information and/or Academic Papers. This can raise doubts about the position and importance of Academic Manuscripts in the preparation of the Draft Regional Regulations. The results of the study state that the position of the Academic Manuscript in the formulation process of the current Regional Regulation formation is a mandatory requirement to provide a scientific basis to support data-based decision-making and objective analysis for the making of Regional Regulations that reflect community participation. After the promulgation of Law Number 13 of 2022, the preparation of Academic Manuscripts not only applies normative juridical and empirical juridical methods, but should also be accompanied by an impact analysis method from the presence of Regional Regulations that are being prepared through the RIA and ROCCIPI methods.